2019
DOI: 10.1177/1948550619843931
|View full text |Cite
|
Sign up to set email alerts
|

Identity Over Time: Perceived Similarity Between Selves Predicts Well-Being 10 Years Later

Abstract: When individuals feel similar to their future self, they are more likely to delay present gratification and make plans for the long run. But do these feelings of similarity actually correspond with heightened well-being for the future self? Theoretically, making patient decisions in the present could lead to a future self who is better off and thus more satisfied. Alternatively, perceived overlap with the future self could cause people to continually deny themselves pleasures in the present, diminishing satisf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 35 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…Prior work has shown that low future self-continuity is a liability for psychological health. For example, low future self-continuity is regarded as a causal factor in depression (Roepke & Seligman, 2015) and is related to severity of psychiatric symptoms (Sokol & Serper 2019a); in contrast, higher future selfcontinuity is positively associated with subjective well-being (increased positive affect, reduced negative affect; Blouin-Hudon & Pychyl, 2015) and satisfaction with life (Reiff et al, 2020;Sokol & Serper, 2019b). Here, we illustrated that high future self-continuity augments meaning by raising authenticity.…”
Section: Discussionmentioning
confidence: 59%
“…Prior work has shown that low future self-continuity is a liability for psychological health. For example, low future self-continuity is regarded as a causal factor in depression (Roepke & Seligman, 2015) and is related to severity of psychiatric symptoms (Sokol & Serper 2019a); in contrast, higher future selfcontinuity is positively associated with subjective well-being (increased positive affect, reduced negative affect; Blouin-Hudon & Pychyl, 2015) and satisfaction with life (Reiff et al, 2020;Sokol & Serper, 2019b). Here, we illustrated that high future self-continuity augments meaning by raising authenticity.…”
Section: Discussionmentioning
confidence: 59%
“…The capacity to generate a positive future might be essential for psychological health and adaptive coping. For example, effective prospection is related to higher subjective well-being (i.e., increased positive affect, decreased negative affect; Blouin-Hudon & Pychyl, 2015) and satisfaction with life (Reiff et al, 2020; Sokol & Serper, 2019; Szabó, 2022), whereas faulty prospection—deficient generation of possible futures, poor evaluation of possible futures, and pessimistic beliefs about these futures—might be a causal factor in depression (Roepke & Seligman, 2015). Faulty prospection might damage self-integrity and thus compromise adaptive functioning.…”
Section: Discussionmentioning
confidence: 99%
“…The long-term associations between future self-identification and later behavioral/psychological outcomes is a relatively unexplored topic. In a recent article, Reiff, Hershfield, and Quoidbach [ 142 ] found that the relatedness component was positively correlated with a measure of well-being (life satisfaction) ten years later. The current results demonstrated that the future self-identification components had different unique relationships with psychological well-being (e.g., self-esteem, hope).…”
Section: Discussionmentioning
confidence: 99%